Analysis of miR-21-5p and miR-144-5p expression as biomarkers in active lung tuberculosis and home contacts - APRILIA PITUT SAVITRI; MUHAMMAD NASRUM MASSI; MOCHAMMAD HATTA; ARIF SANTOSO; MUHAMMAD FACHRI; IRAWATY DJAHARUDDIN; SITTI WAHYUNI; MUHAMMAD ILYAS; HARUN ISKANDAR; ILHAMJAYA PATELLONGI; IRDA HANDAYANI; ISRAINI WIYULANDA ISKANDAR; NAJDAH HIDAYAH; NIRMAWATI ANGRIA; HANDAYANI HALIK (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Savitri AP, Massi MN, Hatta M, Santoso A, Fachri M, Djaharuddin I, Wahyuni S, Ilyas M, Iskandar H, Pattelongi I, Handayani I, Iskandar IW, Hidayah N, Angria N, Halik H. 2025. Analysis of miR-21-5p and miR-144-5p expression as biomarkers in active lung tuberculosis and home contacts. Biodiversitas 26: 831-836. Considering the central role of microRNAs (miRNAs) in development and disease, researchers have proposed that specific circulating miRNAs affect the outcome of tuberculosis (TB) infection and that blood miRNA levels might reflect the course of the disease. This study analyzed the expression of miR-21-5p and miR-144-5p as potential biomarkers in patients with active TB and their household contacts (individuals with latent TB and healthy contacts). This study used a cross-sectional design and enrolled 20 people with active TB, 22 household contacts with positive interferon-gamma release assay results, and 22 healthy controls. miR-21-5p and miR-144-5p expression was examined using quantitative real-time PCR. miR-21-5p expression was more than 37-fold higher in patients with active TB than in healthy contacts. Meanwhile, miR-21-5p expression was approximately 15-fold higher in patients with active TB than in those with latent TB. miR-21-5p expression was 2.5-fold higher in patients with latent TB than in healthy contacts, whereas miR-144-5p expression was 35-fold higher in patients with active TB than in healthy contacts, and approximately 52-fold higher in patients with active TB than in contacts with latent TB. miR-144-5p expression in latent TB was approximately 1.5-fold higher in healthy contacts than in contacts with latent TB. Receiver operating characteristic analysis illustrated that miR-21-5p and miR-144-5p could distinguish latent TB from active TB with areas under the curve of 0.811 (95% Confidence Interval (CI) = 0.67-0.953) and 0.818 (95% CI = 0.689-0.947), respectively. miR-21-5p and miR-144-5p expression was elevated in active TB, highlighting their potential as diagnostic biomarkers.